PENGARUH TEAMWORK TERHADAP KINERJA KARYAWAN (STUDY KASUS PADA PT. XYZ JATINANGOR) - Assyfa Rizka Awalia; Dilla Fania; Diah Utami Setyaningrum (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2020)
Humans are the most important resource in achieving business success aimed at achieving maximum profits. Where, the role of qualified human resources to improve employee performance is a very important factor for the company. The purpose of this study was to determine whether there is an influence of teamwork on the performance of employees of PT. XYZ Jatinangor. The method used is a quantitative method. The sample in this study were 30 employees. The analytical tool used is a simple linear regression method. The results showed that teamwork had a significant positive effect on employee performance at PT. XYZ Jatinangor. This is evident from the t test hypothesis test and also the direction of a positive relationship of group collaboration on performance. This means that teamwork is one of the factors or variables that can affect and improve the performance of employees who work at PT. XYZ Jatinangor.